Photovoltaic performance and impedance spectroscopy of ZnS-Cu-Go nanocomposites. Issue 1 (January 2018) - Aslam, Samia; Mustafa, Faiza; Ahmad, Muhammad Ashfaq; Saleem, Muhammad; Idrees, Muhammad; Bhatti, Arshad Saleem
Abstract: In this work, novel, non-toxic and cost effective ZnS-Cu-GO nanocomposite is synthesized via wet chemical route to study its photovoltaic properties. Three samples including ZnS, ZnS-Cu and ZnS-Cu-GO were prepared and deposited as sensitizers on ZnO coated FTO substrates to assemble PV devices.The samples were characterized using UV–Vis NIR spectroscopy, Atomic force microscopy (AFM).Electrochemical impedance spectroscopy (EIS) and AM 1.5 Sun Simulator. It was observed that ZnS-Cu-GO exhibitedsuperiorchargetransport, remarkably high open circuit voltage(0.8 V) and Fill factor (0.806).The current density significantly enhanced and maximum solar cell efficiency was observed for ZnS-Cu-GO based PV device. A pronounced red shift of 360 nm in the absorption spectra was observed in the ZnS-Cu-GO due to fine dispersion of GO sheets.The AFM analysis showed that incorporation of GO and Cu maximized grain density and trench like grain boundaries in ZnS-Cu-GO which facilitated charge transport mechanism.A detailed electrochemical impedance study to probe charge dynamics in the prepared PV devices is presented herein.